A Case Study of Classroom Management in an Inclusive School: Teachers' Strategies in Overcoming Bulliying in Early Childhood Education - Yeni, Yeni Dwi herlinawati; Rindaningsih, Ida (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to describe classroom management for students with special needs and teachers' strategies in dealing with bullying in inclusive PAUD. Managing inclusive PAUD is different from regular schools in general. The presence of students with special needs in inclusive PAUD means that classroom learning must be targeted. Bullying is a serious problem for children because it can have a negative impact on its victims, including: Low self-esteem, excessive anxiety, and depression. Childhood is a fundamental period to prevent and stop bullying. The forms of bullying that occur include hitting, taking and snatching food, physical mocking, mocking nature, mocking abilities, ostracism, and incitement. Data was collected using interview, observation, and documentation This research is a type of qualitative research with a case study design. This research shows that classroom management in inclusive PAUD is quite good. This is evidenced by several strategies used by teachers: application of school rules and procedures, giving rewards and consequences, building a pleasant environment, interaction between teachers and students. In terms of structuring the physical condition of the classroom is quite good starting from the seating arrangement, room decoration, lighting and air circulation